Improving effectiveness of the project activity of charitable foundations - E. A. Sokolova; P. V. Zozulya (Вестник университета)
The article discusses improvement of the effectiveness of the project activities of charitable foundations. The authors analyse various approaches to charity and charitable activities and reveal stages of preparation and implementation of sponsorship campaigns for companies (strategic planning; analysis of the internal environment; analysis of the external environment; task setting; project implementation; control of results). At the same time, it is noted that planning, organisation and control of charitable activities require a clear and thoughtful management strategy. In the article, the authors give reasons that make it difficult for citizens of Russia to participate in charity and, considering problems of the functioning of charitable organisations, come to the conclusion that they are negatively affected by financial and economic crises, pandemic, sanctions as well as military operations taking place in the modern world. The work considers the strategy of increasing the effectiveness of the project activities of the charitable foundation on the example of “Circus and mercy” and differentiation of its activities. The authors describe the main measures contributing to the development of strategies for promoting the charitable foundation. According to the authors, conditions are also needed within the country for scaling ideas and new developments.